ETIKA ISLAM DALAM PELAKSANAAN GOOD CORPORATE GOVERNANCE DAN DAMPAKNYA TERHADAP KEPUASAN MASYARAKAT DI PUSKESMAS BANJARAN KOTA - hidayat, gagan; Nurani, Asri; jumiati, mia; Sopiah, Evi (LPPM Universitas Islam Indragiri, 2025)
Public healthcare services at the puskesmas (community health center) level play a strategic role in improving community welfare, thereby requiring the implementation of good governance through the principles of Good Corporate Governance (GCG). The urgency of GCG in public services, particularly in puskesmas, is closely related to the need for transparency, accountability, fairness, and responsibility in the delivery of healthcare services. Nevertheless, in practice, various public complaints regarding service quality are still found, such as delays in service delivery, lack of information transparency, and the attitudes of service personnel that do not fully reflect excellent service standards. Therefore, Islamic ethics become important as a moral foundation in the governance of public healthcare services, as they emphasize values such as trustworthiness (amanah), honesty, justice, openness, and responsibility, which are highly relevant to the principles of GCG. This study aims to: (1) analyze the implementation of Islamic ethics in the application of Good Corporate Governance (GCG) at Puskesmas Banjaran Kota; (2) analyze public perceptions and levels of community satisfaction with the services of Puskesmas Banjaran Kota; and (3) analyze the relationship between Islamic ethics and the implementation of GCG in improving the quality of services at Puskesmas Banjaran Kota. The research employs a mixed-methods approach, combining qualitative and quantitative methods. The results indicate that Islamic ethical values have been reflected in the implementation of service bureaucracy at Puskesmas Banjaran Kota and are aligned with GCG principles, particularly transparency, accountability, fairness, independence, and responsibility. Public perceptions of puskesmas services show a generally positive tendency, although several aspects still require improvement. Furthermore, the findings suggest that the integration of Islamic ethics and GCG contributes significantly to improving service quality, strengthening public trust, and enhancing community satisfaction with public healthcare services.